PENGEMBANGAN SISTEM MONITORING DAN KONTROL PERALATAN LISTRIK RUMAH TANGGA BERBASIS INTERNET OF THINGS (IOT) MENGGUNAKAN ESP-01S DAN PZEM-004T - Adnan Zulkarnain; Miftahul Miftahul (Universitas Citra Bangsa, 2025)
The high energy consumption in the residential sector calls for technology-driven solutions to improve efficiency and user control. This research develops an Internet of Things (IoT)-based system for monitoring and controlling household electrical appliances using ESP-01S and the PZEM-004T sensor. The system comprises a monitoring module, control module, API server, and Android application. Electrical parameters are transmitted in real-time to a web server and displayed on the mobile interface, which also allows ON/OFF device control. Testing shows the system is accurate and responsive, with an average measurement error of less than 2% compared to conventional instruments. This system offers a scalable and cost-effective approach to household energy management using IoT.